Efeito da dexametasona na asma experimental induzida em filhote de ratos - Soler, Fernanda Paula Martins (2021)
According to the World Health Organization (WHO), more than 340 million people conform to asthma. Asthma is a chronic disease characterized by bronchoconstriction, increased mucus secretion and bronchial hyperreactivity, which result from the release of inflammatory mediators at the site. Although the treatment of asthma has evolved a lot in recent decades with the treatment of oral and inhaled corticosteroids, a part of asthmatic patients does not induce treatment, requiring high doses of corticosteroid therapy or severely refractory asthma sheath. Thus, it is reasonable to assume that studies aimed at promoting hyperreactivity in rat pups can be interesting tools for understanding glucocorticoid-resistant asthma. In this sense, our objective was to investigate a pulmonary repercussion of the exposure of rat pups with experimental induced asthma. To this end, we divided rat pups into 3 different groups: a control group, a group exposed to ovalbumin to trigger the animal's innate immune response, and a group exposed to ovalbumin and treated with dexamethasone to mimic glucocorticoid-resistant asthma. Total and differential inflammatory cell counts in the bronchoalveolar lavage of the lungs of rat pups were performed, and their lungs were collected for histopathological analysis. Our result was an increase in total and mononuclear cells without bronchoalveolar lavage in the lungs of animals treated with dexamethasone, an increase in polymorphonuclear cells in the group treated with dexamethasone compared to the control group, but there was no increase compared to the group exposed to ovalbumin. In the morphometric analysis, our result showed an increase in total cellularity in the group exposed to ovalbumin compared to the control and a difference in relation to the group treated with dexamethasone. A decrease in mucus was evidenced in the lungs treated with dexamethasone, however undifferentiated in relation to mast cell degranulation, suggesting the activation of a distinct Th2 pathway, and in-depth studies of the immunological profile to assist guests impacted with glucocorticoid-refractory asthma were examined.